Development of E-Module Based on Guided Inquiry Learning (GIL) Integrated Ethnoscience Tape Uli Betawi to Improve Science Literacy of Junior High School Students - Maulida Almas; Sentot Budi Rahardjo; Muzzazinah Muzzazinah (Journal of Educational Sciences, 2026)
This research resulted in an E-module based on Guided Inquiry Learning (GIL) integrated ethnoscience tape uli Betawi to improve the science literacy of Junior High School students. The aim of the study was to determine the feasibility and effectiveness of ethnoscience e-module to improve science literacy of junior high school students. ADDIE development model was used with five stages: Analyze, Design, Development, Implementation, and Evaluation. The research data were taken using a questionnaire and test method. The analysis stage aims to obtain information as reference material for product development. The design stage is carried out the development of E-module content and storyboards by adjusting the concept map of the material that will be used to produce the draft product. The development stage involves expert validation consisting of expert lecturers and teachers as science learning practitioners. The validation results showed that e-module was suitable for use in classroom learning, with valid results in terms of media, language, learning and material aspects. The improvement in science literacy was calculated using the N-gain test, with moderate results for experimental class and low results for control class. Therefore, ethnoscience e-module was deemed feasible and effective in improving science literacy of junior high school student.